Morphological characterisation of Cucurbita maxima Duchesne (Cucurbitaceae) landraces from the Po Valley (Northern Italy) - Orsenigo, Simone; Abeli, Thomas; Schiavi, Massimo; Cauzzi, Paolo; Guzzon, Filippo; Ardenghi, Nicola M.G.; Rossi, Graziano; Vagge, Ilda (Italian Journal of Agronomy, 2018)
Identifying crop genetic resources represent an important aspect of agricultural biodiversity conservation. However, conservation of landraces is challenging because they often cannot be properly identified, or have already suffered from genetic erosion, or have disappeared. Identification of landraces can be obtained using molecular markers or discriminating qualitative and quantitative morphological traits. The latter methodology is cheap and easily achievable, allowing the registration of landraces in national catalogues. In this study, we carried out a morphological characterisation of different accessions of Cucurbita maxima (Cucurbitaceae) cultivated in the Po Valley (N-Italy), locally known as Cappello da prete. The aim was to explore the morphological fruit variability among accessions and to identify potential distinct landraces within the Cappello da prete squash group. Differences between accessions were found indicating that morphological traits can be effectively used to identify these landraces and suggesting a diversification by isolation. Indeed, our morphological analysis shown the existence of two different landraces of Cappello da prete squashes. The adopted procedure can demonstrate that few low-cost traits are useful for the registration of local varieties in the official catalogue of landraces. Our study also demonstrates that morphological characterisation allows a rapid and cost-effective identification of diagnostic morphological traits that, together with historical and cultural information, are fundamental to recognise landraces.